2016
DOI: 10.1007/s12032-016-0791-3
|View full text |Cite
|
Sign up to set email alerts
|

Expression level and methylation status of three tumor suppressor genes, DLEC1, ITGA9 and MLH1, in non-small cell lung cancer

Abstract: Despite therapeutic advances, lung cancer remains one of the most common causes of cancer-related death in the world. There is a need to develop biomarkers of diagnostic and/or prognostic value and to translate findings in basic science research to clinical application. Tumor suppressor genes (TSGs) represent potential useful markers for disease detection, progression and treatment target. We tried to elucidate the role of three 3p21.3 TSGs: DLEC1, ITGA9 and MLH1, in non-small cell lung cancer (NSCLC). We asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 29 publications
0
22
0
Order By: Relevance
“…In contrast to 3q gains in LUSC, a loss of most or all of 3p characterized both LUAD and LUSC, being more prominent in LUSC (Figure ). Losses of 3p were the first cytogenetic alteration found in lung cancers, occurring early during lung cancer pathogenesis, and multiple tumor suppressor genes are located in this region …”
Section: Resultsmentioning
confidence: 99%
“…In contrast to 3q gains in LUSC, a loss of most or all of 3p characterized both LUAD and LUSC, being more prominent in LUSC (Figure ). Losses of 3p were the first cytogenetic alteration found in lung cancers, occurring early during lung cancer pathogenesis, and multiple tumor suppressor genes are located in this region …”
Section: Resultsmentioning
confidence: 99%
“…37 And frequent simultaneous methylation of DLEC1, ITGA9, and MLH1 in more than 50% NSCLC patients indicated the possibility of considering them as a panel of epigenetic markers in NSCLC. 31 However, Geng et al 39 found no significant differences in MLH1 methylation between AC and SCC in Chinese population. Coincidentally, in our case-control study in Chinese, MLH1 methylation difference was not statistical significance between AC and SCC.…”
Section: Discussionmentioning
confidence: 97%
“…Our ROC test indicated that MLH1 MSP method is a sensitive but not specific diagnostic method for NSCLC. Previous studies showed a panel of biomarkers for NSCLC . Recently, miRNA appeared to be valuable diagnostic candidate biomarkers which were employed for the diagnosis of NSCLC in early stages .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations